A rare case of unruptured tubal ectopic pregnancy at 14 weeks gestation with live foetus in situ and review of literature - Biswas, Jayanta K.; Tewari, Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ectopic pregnancy is a condition, where the fertilized ovum implants anywhere other than normal uterine cavity. It is life threatening emergency condition and it can present in diverse ways. More than 95% of ectopic pregnancies usually occur in fallopian tube, ampulla being commonest site of tubal ectopic pregnancy. Diagnosis with location of pregnancy is usually possible by ultrasonography in 1st trimester. However, in most of the developing countries with limited resources, many women do not undergo ultrasonography and medical examination in early pregnancy, leading to late diagnosis. It may lead to life threatening presentation of ectopic pregnancy. Reported average duration of diagnosis of unruptured tubal ectopic pregnancy is usually between 5 to 9 weeks of gestation. Very rarely tubal ectopic pregnancy can remain asymptomatic and unruptured for longer than this usual period of gestation. The reported case is a rare case of viable, unruptured tubal ampullary ectopic pregnancy of 14 weeks of gestational age.